Diluting holy writ: from the 'men of 1914' to the beat generation. Issue 9 (1st September 2020) - Stevenson, Guy
ABSTRACT: This essay explores the paradox between progressive and reactionary forces in inter-war European modernism through parallels between the London-based writers T.E. Hulme, Wyndham Lewis and Ezra Pound, and between Pound and Lewis' avant-garde art group The Vorticists and the American pre-Beatnik Henry Miller. How did the artistic quest to respect and delineate difference lead writers like Pound and Louis-Ferdinand Céline towards a fascist politics that abhorred it? At the other end of the political spectrum, how do the utopian, radically humanist ideals of a writer like Henry Miller find expression through confrontationally anti-humanist language? The answers to these questions, I argue, shed unexpected light on the politics of the American counterculture after World War Two, a moment that is too often understood in unquestioningly progressive terms.